A new quasilinear saturation rule for tokamak turbulence with application to the isotope scaling of transport. (1st September 2022) - Dudding, H.G.; Casson, F.J.; Dickinson, D.; Patel, B.S.; Roach, C.M.; Belli, E.A.; Staebler, G.M.
Abstract: A new quasilinear saturation model SAT3 has been developed for the purpose of calculating radial turbulent fluxes in the core of tokamak plasmas. The new model is shown to be able to better recreate the isotope mass dependence of nonlinear gyrokinetic fluxes compared to contemporary quasilinear models, including SAT2 (Staebler et al 2021 Nucl. Fusion 61 116007), while performing at least as well in other key equilibrium parameters. By first quantifying the isotope scaling of gyrokinetic flux spectra, it is shown that the deviation from the gyroBohm scaling of fluxes originates primarily in the magnitude of the saturated potentials. Using this result SAT3 was formulated using observations made from gyrokinetic data, including a novel and robust relation between the 1D potential spectrum and the radial spectral widths. This serves to define the underlying functional forms of SAT3 before then connecting to the linear dynamics, including a difference in saturation level between ITG- and TEM-dominated turbulence, with the resulting free parameters having been fit to a database of high-resolution nonlinear CGYRO simulations. Additional features outside of the database are included, including E × B shear and multi-ion plasma capability. The methodology used in the development of SAT3 represents an algorithm which can be used in the improvement and generation of future saturation models.